Identification and expression of a new Ly6 gene cluster in zebrafish Danio rerio, with implications of being involved in embryonic immunity. (July 2016) - Wang, Man; Li, Lingyi; Guo, Quanyang; Zhang, Shicui; Ji, Dongrui; Li, Hongyan
Abstract: Lymphocyte antigen-6 (Ly6) superfamily is a large family of proteins and characterized by precisely spaced cysteine motifs, termed the three-finger fold. To date, a large number of members of the Ly6/uPAR family were identified among many species. In this study, we first report the identification and characterization of the secreted Ly2.1-3 proteins on the chromosome 2 in zebrafish and determine the expression pattern. Ly2.1-3 all possess a conserved LU domain and adopt similar three-finger structure with human CD59, SLURP1 and other Ly6 family members. Ly2.1-3 cluster on chromosome 2 and share high homology, possibly originated from chromosomal gene duplication. Ly2.1-3 exhibit distinct expression pattern in the endoderm, they were found abundantly and specifically in the digestive tract, liver and pancreas respectively. The differential expression pattern may suggest Ly2.1-3 acquire new function during gene duplication. The expression level of Ly2.1-3 were up-regulating challenged with LPS indicated that they have a role in innate immune responses of the digestive system during endotoxin challenge in early stage. Highlights: Three secreted Ly-6 members, are identified in zebrafish. Ly2.1-3 are expressed in zebrafish digestive system. LPS up-regulate the expression level of Ly2.1-3.